login
Constant term of the reduction by x^2->x+2 of the polynomial p(n,x) defined below in Comments.
5

%I #13 Feb 05 2016 06:47:48

%S 0,2,14,118,1210,14730,208110,3350550,60580170,1215657450,26813382750,

%T 644830644150,16793095369050,470839138619850,14140985865756750,

%U 452938463797569750,15412288335824630250,555226177657611710250,21111260070730770690750

%N Constant term of the reduction by x^2->x+2 of the polynomial p(n,x) defined below in Comments.

%C The polynomial p(n,x) is defined by recursively by p(n,x)=(x+2n)*p(n-1,x) with p[0,x]=x. For an introduction to reductions of polynomials by substitutions such as x^2->x+2, see A192232.

%F a(n) = (2/3)*(2^n(n+1)! - (2n-1)!!). - _Vaclav Potocek_, Feb 04 2016

%e The first four polynomials p(n,x) and their reductions are as follows:

%e p(0,x)=x -> x

%e p(1,x)=x(2+x) -> 2+3x

%e p(2,x)=x(2+x)(4+x) -> 14+17x

%e p(3,x)=x(2+x)(4+x)(6+x) -> 118+133x.

%e From these, read

%e A192457=(0,2,14,118,...) and A192459=(1,3,17,133,...)

%t q[x_] := x + 2; p[0, x_] := x;

%t p[n_, x_] := (x + 2 n)*p[n - 1, x] /; n > 0

%t Table[Simplify[p[n, x]], {n, 0, 5}]

%t reductionRules = {x^y_?EvenQ -> q[x]^(y/2),

%t x^y_?OddQ -> x q[x]^((y - 1)/2)};

%t t = Table[FixedPoint[Expand[#1 /. reductionRules] &, p[n, x]], {n, 0, 30}]

%t Table[Coefficient[Part[t, n], x, 0], {n, 1, 16}] (* A192457 *)

%t Table[Coefficient[Part[t, n]/2, x, 0], {n, 1, 16}] (* A192458 *)

%t Table[Coefficient[Part[t, n], x, 1], {n, 1, 16}] (* A192459 *)

%Y Cf. A192232, A192459, A192458.

%K nonn

%O 0,2

%A _Clark Kimberling_, Jul 01 2011